Menyoal fatwa MUI (Majelis Ulama Indonesia) Nomor 31 Tahun 2020 perspektif hukum islam - Muizzuddiin, Muhammad Abdul Muqtadir (Maliki Interdisciplinary Journal, 2024)
The Covid-19 pandemic, which occurred at the end of 2019, had a significant impact on people’s lives. Starting from the health sector which is mainly affected by this pandemic, then also in various other sectors of community life such as education and the economy, even in the religious sector. In this article, the main topic of discussion is a fatwa from MUI (Indonesian Ulema Council) No. 31 of 2020, which contains the Implementation of Friday Prayers and Congregations to Prevent the Transmission of the Covid-19 Outbreak. The purpose of writing this article is to explore what is in the MUI fatwa. The research method used in writing this article uses literature research methods (Libraray Research). The result of the discussion of this article is, related to the stretching of saf prayer in congregation the law is legal, related to the implementation of Friday prayers due to physical distancing restrictions so that worshippers can perform Friday prayers other than in mosques such as halls, prayer rooms, sports halls etc., and the last is the law of using masks or mouth coverings when praying, is makruh, because of the existence of hajat syar’iyyah which requires to use masks.